Ketamine Use for Cancer and Chronic Pain Management - Culp, Clayton; Kim, Hee Kee; Abdi, Salahadin (Frontiers in Pharmacology, 2021)
Ketamine, an N-methyl-D-aspartate receptor antagonist, is widely known as a dissociative anesthetic and phencyclidine derivative. Due to an undesirable adverse event profile when used as an anesthetic it had widely fallen out of human use in favor of more modern agents. However, it has recently been explored for several other indications such as treatment resistant depression and chronic pain. Several recent studies and case reports compiled here show that ketamine is an effective analgesic in chronic pain conditions including cancer-related neuropathic pain. Of special interest is ketamine’s opioid sparing ability by counteracting the central nervous system sensitization seen in opioid induced hyperalgesia. Furthermore, at the sub-anesthetic concentrations used for analgesia ketamine’s safety and adverse event profiles are much improved. In this article, we review both the basic science and clinical evidence regarding ketamine’s utility in chronic pain conditions as well as potential adverse events.